2010
DOI: 10.1007/s00405-010-1287-y
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking and self-assessed upper airway health

Abstract: Habitual smoking represents a chronic insult to the airway. However, the effects of smoking on upper airway health remains poorly described. Our objective was to examine the relationship between cigarette smoking and self-assessed upper airway health and evaluate dose-response relationships between exposure and complaints in a sample of 2,523 patients. Eligible subjects were adults referred to ENT specialist for evaluation of chronic nasal or sleep-related complaints. Thirteen specific symptoms and conditions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…21 It is unclear if these effects are temporary or permanent. 4,22 A literature review by Reh et al concluded that cigarette smoke – both active and secondhand—does contribute to CRS pathogenesis. 3…”
Section: Discussionmentioning
confidence: 99%
“…21 It is unclear if these effects are temporary or permanent. 4,22 A literature review by Reh et al concluded that cigarette smoke – both active and secondhand—does contribute to CRS pathogenesis. 3…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, questionnaires that assess the influence of air pollution exposure on the airways have been used previously [21-24], using specific symptoms attributable to acute air pollution exposure as recommended by the American Thoracic Society [25]. For example, airway narrowing due to inflammation and excessive mucous secretion (as an immune response to airway irritation by pollutants) can induce coughing and chest tightness or wheezing, as well as reduce lung function indicated by lowered peak expiratory flow rates [26].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study questions about the following 9 symptoms PNIF value of 120 -140 L/min. among healthy subjects (20,21) .…”
Section: Nose Symptom Visual Analogue Scale (Nose-vas)mentioning
confidence: 97%
“…VAS is a psychometric response scale to measure the intensity of various symptoms. Nose-VAS is a questionnaire developed to be used to quantify the patient reported level of nasal obstruction, as well as other sino-nasal related symptoms on a 100 mmm linear scale ranging from no obstruction/no symptom to complete obstruction/ most intense symptom possible (20) . In the present study questions about the following 9 symptoms PNIF value of 120 -140 L/min.…”
Section: Nose Symptom Visual Analogue Scale (Nose-vas)mentioning
confidence: 99%